2020
DOI: 10.1177/0886260520938516
|View full text |Cite
|
Sign up to set email alerts
|

Identification With the Aggressor and Inward and Outward Aggression in Abuse Survivors

Abstract: Childhood abuse survivors may display both inward and outward aggression manifested in self-injurious behavior (SIB) and violent acts toward others. Scrutinizing the literature reveals that the relational dynamics between victims and their perpetrators might be involved in these phenomena. Yet, research on this subject matter has been sparse. Filling this gap, this study investigated the contribution of the singular bonds between victims and their perpetrators, known as identification with the aggressor, in ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Third, as part of IWA, victims may internalize the perpetrator's aggression and may direct this aggression both inward and outward (Frankel, 2002;. Finally, victims who identify with their abusers may adopt their perpetrator's experience concerning the abuse; they may come to mold themselves to their perpetrators, and to view the abuse from their abuser's perspective-namely, to rationalize or deny the abuse while at the same time experiencing selfblame and self-hatred Lahav et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Third, as part of IWA, victims may internalize the perpetrator's aggression and may direct this aggression both inward and outward (Frankel, 2002;. Finally, victims who identify with their abusers may adopt their perpetrator's experience concerning the abuse; they may come to mold themselves to their perpetrators, and to view the abuse from their abuser's perspective-namely, to rationalize or deny the abuse while at the same time experiencing selfblame and self-hatred Lahav et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 60% of the participants reported having suffered more than one of the five types of maltreatment in their childhood. When compared to the prevalence of child maltreatment measured in the same way among college samples in other countries (e.g., the United States, Canada, Turkey, and Israel; emotional abuse, 22.8–46.9%; emotional neglect, 25–49%; physical abuse, 15.2–42.9%; physical neglect, 16.3–32.7%; sexual abuse, 11.4–40.1%; Kircaburun et al, 2020; Lahav et al, 2022; Lahav et al, 2019; Mathews et al, 2008; Paivio & Cramer, 2004; Şar et al, 2019), we found a higher prevalence of emotional and physical neglect.…”
Section: Resultsmentioning
confidence: 99%
“…In the hope that they would be permitted to survive, they used their strong capacity for empathy and identification to reshape their beliefs and behaviors to fit the ideal image of themselves in the mind of their parents (i.e., the attacker). Thus, their risk-taking, self-harming, and punitive behaviors can be seen as manifestations of identifying with the perpetrator in abuse situations (Lahav et al, 2022) and internalization of the "malignant self-object" (Kohut, 1971) in order to survive. Nevertheless, at the same time, they introjected aspects of external reality and created fantasies that helped them live in the external reality (Frankel, 2002).…”
Section: Discussionmentioning
confidence: 99%